Valoracion de la efectividad del glyphosate en viveros de pinus caribaea var. caribaea - Betancourt Riquelme, M.A.=700 1 Montalvo Guerrero, J.M.
(Es, En)
Ilus., 9 ref.
Keywords: PINUS CARIBAEA; HERBICIDAS; MALEZAS; CUBA